Mitochondrial involvement in PC: improving therapeutic strategies - Zhang, Jiaxin; Lou, Chang (Frontiers in Pharmacology, 2025)
Prostate cancer (PC) is a complex disease propelled by various molecular mechanisms. The role of mitochondria in PC has recently emerged as a significant research focus. Mitochondria, often referred to as the cell’s powerhouses, are not only essential for energy production but also crucial for key cellular processes like apoptosis, oxidative stress, and metabolic reprogramming. Changes in energy metabolism, marked by an increased dependency on oxidative phosphorylation (OXPHOS), have been noted in PC cells, offering a potential therapeutic target. Moreover, specific mitochondrial DNA (mtDNA) mutations have been linked with advanced tumors and adverse patient outcomes in PC. The mitochondrial reactive oxygen species (ROS), the disruption of mitochondrial dynamics and the fine balance between pro-apoptotic and anti-apoptotic signals mediated by Bcl-2 family proteins have also been implicated in PC. Comprehending the complex interaction between mitochondria and PC biology offers substantial potential for creating innovative targeted therapeutic strategies. This review emphasizes the role of mitochondria in the occurrence and malignant progression of PC, as well as the potential of targeted interventions on mitochondria in developing treatments, which may improve the prognosis of PC patients.